2015
DOI: 10.1039/c5cp01493j
|View full text |Cite|
|
Sign up to set email alerts
|

Molecular and ionic diffusion in aqueous – deep eutectic solvent mixtures: probing inter-molecular interactions using PFG NMR

Abstract: Pulsed field gradient (PFG) NMR has been used to probe self-diffusion of molecular and ionic species in aqueous mixtures of choline chloride (ChCl) based deep eutectic solvents (DESs), in order to elucidate the effect of water on motion and inter-molecular interactions between the different species in the mixtures, namely the Ch + cation and hydrogen bond donor (HBD). The results reveal an interesting and complex behaviour of such mixtures at a molecular level. In general, it is observed that the hydroxyl prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

19
226
4
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 222 publications
(253 citation statements)
references
References 29 publications
19
226
4
4
Order By: Relevance
“…Therefore, above this point, it is inappropriate to describe the system as a DES, and it should instead be considered as a solution of DES components in water. Importantly, this nanostructure transition point correlates with trends in the physical properties of cholinium DES/water mixtures 8, 12, 23…”
mentioning
confidence: 77%
See 3 more Smart Citations
“…Therefore, above this point, it is inappropriate to describe the system as a DES, and it should instead be considered as a solution of DES components in water. Importantly, this nanostructure transition point correlates with trends in the physical properties of cholinium DES/water mixtures 8, 12, 23…”
mentioning
confidence: 77%
“…This explains the tolerance of the DES nanostructure and properties towards hydration, and can be related to the solvophobic accommodation of solutes in ILs;2 “solvent‐separated ion pairs” are seen in many IL/cosolvent mixtures 21. A transient water‐rich sequestered domain around choline helps to rationalize the unusual properties of hydrated DESs, such as low water activity23 and a high water self‐diffusion coefficient 12. The retention of the DES “pseudo‐IL” character at such low ionic strengths is remarkable.…”
mentioning
confidence: 97%
See 2 more Smart Citations
“…12 Recent diffusion studies on aqueous choline chloride-based DES were able to show that some of these liquids are inhomogeneous at a macroscopic level and it was observed that the addition of water significantly changes the molecular and ionic interactions between the different species. 13 For example, in some cases, the hydroxyl protons of the hydrogen bond donor behave differently from its parent molecule when water is added to the system. Electrical conductivity, density and viscosity measurements of relatively dilute alkali metal halides and glycerol have been previously carried out.…”
Section: Introductionmentioning
confidence: 99%